GENERATIONAL WORLDVIEW DIFFERENCES AND SOCIO PSYCHOLOGICAL ASPECTS OF ACCEPTING AND MANAGING INTERGENERATIONAL CONFLICTS (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article examines the differences in worldviews, values, and behavioral patterns among contemporary generations—Baby Boomers, Generation X, Generation Y (Millennials), Generation Z, Generation Alpha, and Generation Beta. Special attention is given to intergenerational conflicts arising from technological advancement, value divergence, and communication styles. The study is supported by statistical data from official and reputable sources, and it proposes constructive approaches to accepting and managing generational conflicts in modern society.